Phonostylistics of Verbs in English: A Comprehensive Analysis - Shahnoza, Sulaymonova (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the phonostylistic variations exhibited by verbs in the English language. Phonostylistics, a branch of linguistics, investigates the stylistic effects produced by phonetic features of language. This article presents a thorough examination of phonetic characteristics influencing the stylistic nuances of English verbs. Through a combination of qualitative and quantitative analysis, the study aims to contribute to our understanding of the intricate relationship between phonetics and style in verb usage